2021
DOI: 10.1002/eco.2348
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of the circumferential variation of stemflow inputs on the boles of Pinus sylvestris L. (Scots pine)

Abstract: The spatial variability of stemflow on the bole of trees has rarely been the focal point of stemflow studies, despite its potential importance for stemflow-induced changes to soils. This study helps close this data gap by supplying quantitative data on possible drivers of circumferential variation of stemflow on the boles of two Pinus sylvestris L. (Scots pine). Hence, the objectives of the present study were to quantify the circumferential spatial variability of stemflow on tree stems and to assess how some b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In this case, the main constraint of the sampling design was the need to collect samples every 24 h, which is suitable for sampling particularly large storm events such as typhoons but not for continuous monitoring of rainfall events in more remote areas. In addition, the synchronized and continuous 1 h sampling time interval may not always be well suited to capturing all the rainfall, throughfall and especially stemflow isotopic composition variability throughout the event, as stemflow production is often concentrated within a short period during the rainfall event, once a gross rainfall threshold has been exceeded (Cayuela et al, 2018b; Pinos et al, 2021). The third and, we believe, most recent study of the intra‐storm isotopic composition of rainfall, throughfall and stemflow was carried out by Tao et al (2017) for two rainfall events.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the main constraint of the sampling design was the need to collect samples every 24 h, which is suitable for sampling particularly large storm events such as typhoons but not for continuous monitoring of rainfall events in more remote areas. In addition, the synchronized and continuous 1 h sampling time interval may not always be well suited to capturing all the rainfall, throughfall and especially stemflow isotopic composition variability throughout the event, as stemflow production is often concentrated within a short period during the rainfall event, once a gross rainfall threshold has been exceeded (Cayuela et al, 2018b; Pinos et al, 2021). The third and, we believe, most recent study of the intra‐storm isotopic composition of rainfall, throughfall and stemflow was carried out by Tao et al (2017) for two rainfall events.…”
Section: Introductionmentioning
confidence: 99%
“…5). It was found that the great bark water storage capacity of forests could result in the further delay of TF and SF onset (Levia and Herwitz, 2005;Levia et al, 2010;Li et al, 2016;Pinos et al, 2021). In summary, the different intra-event TF and SF dynamics between species were attributed to a complex interaction of biotic and abiotic factors (Yuan et al, 2019;Zhang et al, 2018;Levia et al, 2010).…”
Section: Rainfall Partitioning and Influencing Factors At The Intra-e...mentioning
confidence: 96%
“…For the four studied trees, the simulated stemflow yield of 36.5 L (equivalent to a rainfall of $12 mm) produced a mean funnelling ratio (per basal area) F P,Bt of 46.5 ± 1.8 (Figure 5). The heterogeneity of stemflow infiltration areas has been attributed, at least partly, to the heterogeneity of stemflow channelled along preferred flowpaths of the tree bole (e.g., Herwitz, 1988;Imamura et al, 2017;Levia et al, 2011) due to variations in the structure of the tree crown, branch distribution and angles, lean of the stem (e.g., Dunkerley, 2014;Imamura et al, 2017), or by the heterogeneities in the roughness of the bark of the trunk (Levia & Germer, 2015;Pinos et al, 2021). In our study, to restrict the unknowns, we decided to simulate uniformly distributed stemflow around the trunk, but, despite the fact that we applied simulated stemflow from just 0.7 m above the surface, we still observed marked spatial heterogeneities of the stemflow on the trunk as well as the stemflow input to the soil around the stems.…”
Section: Basal Area and Infiltration Area Funnelling Ratiosmentioning
confidence: 99%